2004
DOI: 10.1002/anie.200353557
|View full text |Cite
|
Sign up to set email alerts
|

The Chemistry of CaII and YbII: Astoundingly Similar But Not Equal!

Abstract: The structures and chemical behavior of heavier alkalineearth metal complexes (Ca, Sr, and Ba) [1] have often been compared to that of early d-and f-block metal complexes. [2][3][4][5][6][7][8][9][10][11] In particular, parallels with "hot" lanthanide(ii) complexes [12] have been observed. Lanthanide complexes are d 0 species with a limited radial extension of their f orbitals. Therefore, orbital factors do not affect their chemistry as much as in transition-metal chemistry. As for complexes of the heavier al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
99
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(110 citation statements)
references
References 47 publications
11
99
0
Order By: Relevance
“…Keywords: homogeneous catalysis · lanthanides · polymerization · reaction mechanisms · styrene based on ytterbium, [8] scandium, [9] and neodymium [10] were shown to feature very high activity and syndiospecificity. In particular, some of us reported that neutral allyl neodymocene complexes of general formula [{Cp''CMe 2 Flu'}NdA C H T U N G T R E N N U N G (h 3 -allyl)A C H T U N G T R E N N U N G (ether) n ] (Cp'' = 3-R 1 C 5 H 3 , R 1 = H (Cp'), tBu; Flu' = 9-C 13 H 8 ; allyl = CH 2 CHCH 2 ; ether = THF, Et 2 O, n = 0,1) (1) are single-component (i.e., they do not require any co-activator), single-site catalysts which are effective under industrially relevant conditions (bulk styrene, high temperature);…”
Section: Introductionmentioning
confidence: 99%
“…Keywords: homogeneous catalysis · lanthanides · polymerization · reaction mechanisms · styrene based on ytterbium, [8] scandium, [9] and neodymium [10] were shown to feature very high activity and syndiospecificity. In particular, some of us reported that neutral allyl neodymocene complexes of general formula [{Cp''CMe 2 Flu'}NdA C H T U N G T R E N N U N G (h 3 -allyl)A C H T U N G T R E N N U N G (ether) n ] (Cp'' = 3-R 1 C 5 H 3 , R 1 = H (Cp'), tBu; Flu' = 9-C 13 H 8 ; allyl = CH 2 CHCH 2 ; ether = THF, Et 2 O, n = 0,1) (1) are single-component (i.e., they do not require any co-activator), single-site catalysts which are effective under industrially relevant conditions (bulk styrene, high temperature);…”
Section: Introductionmentioning
confidence: 99%
“…Attention then turned towards the preparation of heteroleptic calcium(II) amides and alkyls that could be subsequently treated with iodinating agents to give [{C(3-Ad-5-Mepz) 3 ly) and display similar coordination chemistry. [20] Therefore, it seemed unlikely that a stable ytterbium(II) iodide complex incorporating the [C(3-Ad-5-Mepz) 3 [5a] Although no identifiable products could be isolated from any of these reactions, we believe that compound 8 holds significant potential for inorganic chemists as a precursor to related sterically protected ytterbium(II) systems.…”
mentioning
confidence: 99%
“…Because the ionic radii of calcium and ytterbium differ only slightly (Ca(II), 1.00 Å ; Yb(II), 1.02 Å for CN 6) [6], bond distances and angles of the ligands in their respective complexes are usually similar [32]. An argument has been made that the longer Yb-C bonds reflect bond weakening arising from the filled f 14 shell of the Yb(II) ion [4].…”
Section: Analysis Of Metal-ligand Distances In Bulky Allyl Complexesmentioning
confidence: 98%